PERK promotes cancer cell proliferation and tumor growth by limiting oxidative DNA damage - Bobrovnikova-Marjon, Ekaterina (2010)
In order to proliferate and expand in an environment with limited nutrients, cancer cells co-opt cellular regulatory pathways that facilitate adaptation and thereby maintain tumor growth and survival potential. The endoplasmic reticulum (ER) is uniquely positioned to sense nutrient deprivation stress and subsequently engage signaling pathways that promote adaptive strategies. As such, components of the ER stress-signaling pathway represent potential anti-neoplastic targets. However, recent investigations into the role of the ER resident protein kinase PERK have paradoxically suggested both pro- and anti-tumorigenic properties. We have utilized animal models of mammary carcinoma to interrogate PERK contribution in the neoplastic process. The ablation of PERK in tumor cells resulted in impaired regeneration of intracellular antioxidants and accumulation of reactive oxygen species triggering oxidative DNA damage. Ultimately, PERK deficiency impeded progression through the cell cycle due to the activation of the DNA damage checkpoint. Our data reveal that PERK-dependent signaling is utilized during both tumor initiation and expansion to maintain redox homeostasis and thereby facilitates tumor growth.